Nitrogen, phosphorus and potassium in coffee crop in vegetative stage and on brown eye spot management - Vilela, Marina Scalioni (2020)
Coffee crop has great importance in Brazilian agriculture, and one of the most limiting factors for achieving high productivity is balanced plant nutrition, especially in vegetative stage. Mineral nutrition also interferes on the incidence of diseases such as brown eye spot (BES – Cercospora coffeicola), which is favored by nutritional balance. Thus, the aim of this study was to evaluate the different effects of fertilization levels with nitrogen (N), phosphorus (P) and potassium (K), denominated NPK, on growth, development, plant nutrition and on the incidence of BES on coffee crop in vegetative stage. The study was carried out in Lavras-MG, Brazil, in a plantation of the cultivar Mundo Novo IAC 379/19. The experimental design was randomized blocks, with six treatments and four replications. The fertilization levels used were: 10, 40, 70, 100, 130 and 160% of the standard fertilization recommended for NPK. Growth characteristics, leaf water potential, incidence of BES and also chemical analyzes of soil and leaves were evaluated. Differences in plant growth were found from October/2019. The lowest leaf water potential was occurred in July. Climatic conditions influenced the development of coffee and incidence of BES. A reduction in area under the incidence progress curve (AUIPC) was observed with the increase in the dose of NPK. There was also a reduction in the number of leaves due to the increase in the dose of NPK. The levels of NPK fertilization influenced their concentrations in the leaves, as well as other nutrients. Therefore, on the fertilization level of 100% the plants showed balanced foliar contents of nutrients, without harm the growth of coffee crop, besides that, this level favored the reduction of AUIPC, maintaining more leaves and the nutritional balance in coffee plants.